2013
DOI: 10.1016/j.sjopt.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Ocular aberrations in amblyopic children

Abstract: Lower order aberrations remain the major factor that affect retinal image quality and hence amblyopia development especially in ametropic eyes. This can be corrected optically. Studying HOA profile in amblyopic eyes failed to explain why refractory amblyopia does not respond to orthoptic treatments. This outcome indicates that theories of central problems in image processing and binocular interaction are likely the main cause of refractory amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…reported that WTR astigmatism showed a greater reduction in magnitude (emmetropisation) compared to ATR astigmatism. More recent studies investigating total ocular aberrations in children have reported that the magnitude of astigmatism is significantly higher in amblyopes (~1.25 to 2.00 D) compared to non‐amblyopic, emmetropic control groups (~0.25 D). In addition, refractory amblyopes (i.e.…”
Section: Visual and Functional Impact Of Astigmatismmentioning
confidence: 99%
“…reported that WTR astigmatism showed a greater reduction in magnitude (emmetropisation) compared to ATR astigmatism. More recent studies investigating total ocular aberrations in children have reported that the magnitude of astigmatism is significantly higher in amblyopes (~1.25 to 2.00 D) compared to non‐amblyopic, emmetropic control groups (~0.25 D). In addition, refractory amblyopes (i.e.…”
Section: Visual and Functional Impact Of Astigmatismmentioning
confidence: 99%
“…Therefore, we performed measurements under both conditions for the analysis. We selected a 4-mm area of visual-axis HOA analysis, regardless of cycloplegia, because it played the most important role for image quality [ (1,7,9,10,12,13,(22)(23)(24)(25)].…”
Section: Discussionmentioning
confidence: 99%
“…]. However, most of such studies have used a small sample size and measured the HOA by using machines with older technology, and their results have varied highly [ (1,(7)(8)(9)(10)(11)(12)(13)]. A recent novel study using HOA-correcting, real-time, closed-loop adaptive optics perceptual learning system demonstrated BCVA and contrast sensitivity significantly improved in refractive amblyopic eyes in adolescents (mean age, 16 years) [(14)].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amblyopia, a common ophthalmologic disease with a prevalence of 1.6%-3.6%, is considered to be due to insufficient foveal stimulation during a critical period. It has three main types: refractive, strabismic and deprivation amblyopia [1][2][3][4], of which, refractive amblyopia is the most common [5,6].…”
Section: Introductionmentioning
confidence: 99%